DINAMIKA ORGANISASI MAJELIS ADAT BUDAYA MELAYU INDONESIA (MABMI) DALAM MELESTARIKAN BUDAYA MELAYU DI KOTA MEDAN - Raharja, Febrian Syah; Puspitawati, Puspitawati (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2024)
The establishment of the Unitary State of the Republic of Indonesia after the end of the Deli Malay kingdoms, made all government structures and attributes change. Deli Malay culture is increasingly neglected in the city of Medan, which is a multicultural society. Medan is a city that has many overseas communities and comes from various regions. Majelis Adat Budaya Melayu Indonesia (MABMI) was established in 1973, as a forum for the association of traditional leaders who became the shield of Malay customs. The purpose of the research is to find out the problems, challenges and roles carried out by MABMI institutions in preserving Malay culture in Medan City. This research uses a qualitative descriptive method. The results of this study are that the Indonesian Malay Cultural Customary Council has carried out positive planning on the development of Malay culture in Medan City, in accordance with its role as a Community Organization in charge of preserving Malay culture. However, the implementation of Malay cultural development is still not optimal due to the lack of attention of most of the people of Medan City and the younger generation of Malays to their culture.